Investigation of the Interaction of Blood Platelets with the Coagulation System at the Site of Plug Formation In Vivo in Man - Effect of Low-Dose Aspirin - Kyrle, P A; Westwick, J; Scully, M F; Kakkar, V V; Lewis, G P (Thrombosis and Haemostasis, 1987)
In 7 healthy volunteers, formation of thrombin (represented by fibrinopeptide A (FPA) generation, α-granule release (represented by β-thromboglobulin [βTG] release) and the generation of thromboxane B2 (TxB2) were measured in vivo in blood emerging from a template bleeding time incision. At the site of plug formation, considerable platelet activation and thrombin generation were seen within the first minute, as indicated by a 110-fold, 50-fold and 30-fold increase of FPA, TxB2 and PTG over the corresponding plasma values. After a further increase of the markers in the subsequent 3 minutes, they reached a plateau during the fourth and fifth minute. A low-dose aspirin regimen (0.42 mg.kg-1.day-1 for 7 days) caused >90% inhibition of TxB2formation in both bleeding time blood and clotted blood. At the site of plug formation, a-granule release was substantially reduced within the first three minutes and thrombin generation was similarly inhibited. We conclude that (a) marked platelet activation and considerable thrombin generation occur in the early stages.of haemostasis, (b) α-granule release in vivo is partially dependent upon cyclo-oxygenase-controlled mechanisms and (c) thrombin generation at the site of plug formation is promoted by the activation of platelets.
Keywords: Platelet coagulation interaction; Aspirin; Bleeding time